Assessment of Spin in the Abstracts of Systematic Reviews and Meta-analyses on Platelet-Rich Plasma Treatment in Orthopaedics: A Cross-sectional Analysis. Issue 2 (14th February 2023) - Reddy, Arjun K.; Lulkovich, Kaley; Wirtz, Alexis; Thompson, Jay C.; Scott, Jared T.; Checketts, Jake X.; Ottwell, Ryan; Hanson, Chad D.; Hartwell, Micah; Vassar, Matt
Background: Systematic reviews on the use of platelet-rich plasma (PRP) in orthopaedic surgery are abundant in current published literature. However, a beautification of results (referred to as spin ) has been noted in abstracts across various aspects of medicine. Purpose: To determine the prevalence of spin in systematic reviews of PRP-related orthopaedic surgery abstracts. Study Design: Cross-sectional study. Methods: Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and Murad and Wang guidelines, we conducted a search in Medline, Embase, and the Cochrane Database for reviews on PRP-related orthopaedic surgery. The search included studies published from inception until June 30, 2021. Included were systematic reviews written in English that involved the use of PRP in the treatment of orthopaedic injuries in human participants. The abstracts of the included reviews were evaluated for the top 9 types of spin as described by Yavchitz et al in 2016. We determined the relationship between spin and study characteristics using odds ratios. Results: Of an initial 1560 studies, 176 were included. We found that 50 studies (28.4%) contained at least 1 form of spin. The 2 most common forms of spin found in our sample were type 5 ("Conclusion claims the beneficial effect of treatment despite high risk of bias"; n = 27 [15.3%]) and type 3 ("Selective reporting or overemphasis of efficacy in outcomes favoring beneficial effect of intervention"; n = 18 [10.2%]). No statistical significance was found between study characteristics and the presence of spin. Conclusion: Spin was present in 28% of the systematic reviews that covered PRP-related orthopaedic treatments. Spin was not associated with general study characteristics, including adherence to PRISMA guidelines or funding. Journals and authors should be aware of spin in articles and avoid its usage.